Life-creativity of Mykhail Verikivsky: composer's individuality, ideological and aesthetic features and stylistic peculiarities - Demjanchuk, Oleksandr (Professional Art Education, 2022)
The purpose of the article is to highlight the peculiarities of ideological, aesthetic and stylistic searches of M. Verikivskyi's compositional work in the context of general trends in the national musical culture of the first half of the twentieth century. The place and significance of choral art in the works of M. Verikivskyi are revealed.Methods and methodology. The article is based on an art historical and comparative analysis of the creative personality and multidirectionality of M. Verikivskyi's composing activity, choral creativity and musical and stylistic searches.The scientific novelty of the article lies in determining the content and form of M. Verikivskyi's compositional creativity and choral activity in the Kremenets period. Attention is paid to the stylistic features of the composer's choral work (democratic, folk, epic, philosophical). The features of the outstanding composer's innovation in the context of the birth of new choral genres (choral monologues, choral reflections, choral humoresques) are considered.Results. The article presents the content of musical and aesthetic views of the outstanding Ukrainian composer M. Verikivskyi. The interaction of traditions and innovation in the genre varieties of the author's choral works (peasant song folklore and concert choral practice, genre dance choirs and dramatic choral scenes) is investigated.
Keywords: democracy of music; interest to national history; national style forming; piano music; choral works; historical topics; Krememts-Volyn themes; music and aesthetic outlook